2023
DOI: 10.3389/fpsyg.2023.1098974
|View full text |Cite
|
Sign up to set email alerts
|

Network embeddedness, digital transformation, and enterprise performance—The moderating effect of top managerial cognition

Abstract: Under the new background of the explosive growth of digital economy and the deep integration of real economy, how to improve the performance level through digital transformation has become the key for enterprises to achieve high-quality development. Based on the embeddedness theory and the upper echelons theory, this paper studies the logic and mechanism of network embeddedness affecting enterprise performance, in order to describe the pre-motivations and complete influencing paths of digital transformation af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Digital innovation is then further encouraged by digital transformation (Almaazmi et al, 2021). Previous research results have shown that digital transformation has an impact on digital innovation (Li & Fei, 2023;Juhász et al, 2022). The following research hypothesis is then put forth: H1.…”
Section: Digital Transformation and Digital Innovationmentioning
confidence: 97%
See 1 more Smart Citation
“…Digital innovation is then further encouraged by digital transformation (Almaazmi et al, 2021). Previous research results have shown that digital transformation has an impact on digital innovation (Li & Fei, 2023;Juhász et al, 2022). The following research hypothesis is then put forth: H1.…”
Section: Digital Transformation and Digital Innovationmentioning
confidence: 97%
“…Digital innovation encourages the development of new products built on cutting-edge technologies, adding value and giving companies a stronger competitive edge (Khin & Ho, 2019). Effective digital innovation tends to improve new product development, strengthen brand image, produce better goods and services, and boost dependability for businesses (Li & Fei, 2023). The performance of the company is then improved by digital innovation (Chen et al, 2023).…”
Section: Digital Innovation and Firm Performancementioning
confidence: 99%
“…Digital transformation (DT) is defined by various authors as the utilization of new digital technologies, such as social media, mobile, analytics, or embedded devices, to enable significant business improvements (Chanias & Hess, 2016;Fitzgerald et al, 2013;Horlacher & Hess, 2016). These business enhancements may include enhancing customer experience, streamlining operations, creating new business models, and the creation of innovative services (Bekkhus, 2016;Guo et al, 2023;Leischnig et al, 2016;Li, 2022;Li & Fei, 2023;Martínez-Caro et al, 2020;Park & Saraf, 2016;Piccinini et al, 2015;Saldanha et al, 2018;Singh et al, 2021;Yu et al, 2021;Zhai et al, 2022). Digital transformation has brought about significant changes in business processes, and the ability to adapt quickly has emerged as a crucial factor for competitiveness and innovation (Teece, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Prior research verified the DT effect on enterprise performance (Li and Fei, 2023;Ren et al, 2023), Corporate Social Performance (Meng et al, 2022), corporate sustainability (Zhang et al, 2022). However, few researchers investigated the effect on innovation performance.…”
Section: Introductionmentioning
confidence: 98%
“…Zhang et al (2022) tested the relationship between digital transformation and corporate sustainability. Li and Fei (2023) suggested that DT is positively associated with a firm's performance and network embeddedness plays a mediation role.…”
Section: Introductionmentioning
confidence: 99%